Exploring Public Trust in South Africa’s Coalition Politics: The Case of the Government of National Unity - Zoko, Mxolisi Israel (Journal of Ecohumanism, 2025)
South Africa’s coalition politics have become popular as the country navigates a changing political landscape marked by dwindling support for dominating parties. This study examined public trust in coalition governance, using the Government of National Unity (GNU) as a case study. The study employed a qualitative approach to investigate aspects impacting public views, such as public trust and accountability, stability, and policy consistency. Game theory was used as the theoretical basis for this investigation. A purposive sampling strategy was employed to obtain a sample of six individual participants from the Chris Hani District. Data was gathered using a semi-structured interview, and the findings were analysed using thematic content analysis. The findings suggest that coalition governments can enhance diversity and broad representation. However, they frequently confront obstacles such as internal strife and dwindling public trust in their ability to govern efficiently. This study emphasizes the value of transparent governance and unified leadership in building public trust. These findings have important implications for forming and managing future coalition governments in South Africa and other multiparty democracies. This study adds to the existing literature regarding coalition politics and governance discourse by giving a more sophisticated understanding of trust dynamics in transitional democracies.